2021
DOI: 10.1111/ajae.12260
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal agricultural activity and crime

Abstract: Sudden shocks to labor demand have sometimes been shown to increase local crime rates. We build on this literature by estimating the causal effect of labor-intensive seasonal agricultural activity on crime. We analyze a unique data set that describes criminal activity and fruit, vegetable, and horticultural (FVH) employment by month and U.S. county from 1990 to 2016. We find that the FVH labor share is associated with reduced property and violent crime rates, and possibly the number of property crimes committe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…There are many still-unanswered questions regarding how rising wages affect the farm workforce. Other datasets, including the Quarterly Census of Employment and National Agricultural Worker Survey, which have been used in farm labor research, for example, Charlton et al (2022); Richards (2018), may yield additional insights on broader minimum wage impacts, especially if they capture additional or different subpopulations of farm workers. Replicating Cengiz et al (2019) in a data set that captures hourly wages for farm workers would also improve understanding of farm labor market dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…There are many still-unanswered questions regarding how rising wages affect the farm workforce. Other datasets, including the Quarterly Census of Employment and National Agricultural Worker Survey, which have been used in farm labor research, for example, Charlton et al (2022); Richards (2018), may yield additional insights on broader minimum wage impacts, especially if they capture additional or different subpopulations of farm workers. Replicating Cengiz et al (2019) in a data set that captures hourly wages for farm workers would also improve understanding of farm labor market dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…As of 2017, a significant number of large operations in the United States rely on foreign-born workers and nearly 50% of hired crop workers lacked the required immigration status to legally work in the U.S. (USDOL, ETA, 2017;Zahniser et al, 2018). However, available research does not substantiate the fears about immigrant workforce laborers (Barclay, 2001;Charlton et al, 2021;Osborne et al, 2019). In fact, using NIBRS data, Osborne et al (2019) found that perpetrators of farm crime in the U.S. were mostly white men living in the same jurisdiction as those they victimized.…”
Section: Fear Of Crime and Perceptions Of Safety In Rural Communitiesmentioning
confidence: 99%
“…Residents in agricultural communities of California have often objected to building temporary farmworker housing for non-immigrant guest workers because they feared that it would reduce the value of their homes and increase crime rates. Nevertheless, rigorous analysis shows that seasonal, labour-intensive agricultural activity is associated with a reduction in monthly crime rates within counties of the United States of America (Charlton, James and Smith, 2022). However, as seasonal farm workers began to settle in the United States of America with their families, increased agricultural employment was shown to increase immigrant shares in rural areas and vice versa, while both immigration and increased agricultural employment increased local poverty rates (Martin and Taylor, 2003).…”
Section: The Agricultural Transformation and Agrifood Systemsmentioning
confidence: 99%